2016
DOI: 10.1007/s12016-016-8581-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Safety of TNF Inhibitors in Immunoglobulin-Resistant Kawasaki Disease: a Meta-analysis

Abstract: Previous studies showed that tumor necrosis factor (TNF) inhibitors might decrease the rate of coronary artery abnormalities in pediatrics with intravenous immunoglobulin (IVIG)-resistant Kawasaki disease (KD). Therefore, we aimed to evaluate the effect and safety of TNF inhibitors in IVIG-resistant KD. We undertook a meta-analysis of clinical trials identified in systematic searches of PubMed, EMBASE, Cochrane Database, and Google scholar through May 2016. Five studies were included. Overall, rate of coronary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…In 2012, Callinan reported a higher CAL incidence of 19% in California ( 21 ). Several studies have been conducted in order to reduce the occurrence of CAL, for example involving adjunctive corticosteroid therapy, different doses of aspirin, and tumor necrosis factor inhibitors in immunoglobulin-resistant KD ( 3 , 38 , 39 ). Unfortunately, they all failed to find convincing positive results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Callinan reported a higher CAL incidence of 19% in California ( 21 ). Several studies have been conducted in order to reduce the occurrence of CAL, for example involving adjunctive corticosteroid therapy, different doses of aspirin, and tumor necrosis factor inhibitors in immunoglobulin-resistant KD ( 3 , 38 , 39 ). Unfortunately, they all failed to find convincing positive results.…”
Section: Discussionmentioning
confidence: 99%
“…In severe cases, giant coronary artery aneurysms or coronary artery ectasia can develop, which is the leading cause of acquired heart disease ( 1 , 2 ). Intravenous immunoglobulin (IVIG) therapy is the first-line treatment of KD with well-established therapeutic effects in preventing coronary artery abnormalities ( 3 ). Coronary artery aneurysms (CAAs) develop in ~25% of untreated patients ( 4 ); however, in patients receiving a timely high dose of IVIG, it is reported that only about 5% of patients ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of sufficient clinical trials regarding this topic, as well as the small number of subjects included in the available trials, may have led to bias. A meta-analysis in 2017 [32] that included only 4 studies (2 RCTs of immunoglobulin-resistant KD patients, 1 RCT of initial treatment for KD patients, and 1 case-control study) showed that with the exception of antipyretic action, infliximab did not provide significantly more benefit than second IVIG with respect to the cardioprotective effect, rate of treatment resistance, and total rate of AEs. The authors took full advantage of the limited literature in this meta-analysis and merged data from studies with different designs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, according to a study on KD pathogenesis, children suffering from the disease presented with significantly elevated levels of TNFα. In addition, anti-TNFα was tested in the treatment of KD and showed significant improvement [45].…”
Section: Cytokine Profile In Both Disorders Innate Immunity Cytokinesmentioning
confidence: 99%